Reading musical interpretation. Case Studies in Solo Piano Performance - Hellaby, Julian (Farnham Ashgate Publishing, 2009)
Performance studies in the Western art music tradition have often been dominated by the relationship of theoretical score-analysis to performance, although some recent trends have aimed at dislodging the primacy of the score in favour of assessing performance on its own terms. In this book, Julian Hellaby further develops these trends by placing performance firmly at the heart of his investigations and presents a structured approach to analysing the interpretation of a musical work from the perspective of a musically informed listener. A CD of the author's own recordings of the three focal works is included.
Keywords: Piano; Musical interpretation; Keyboard instrument